The haunting of Alma Fielding : a true ghost story - Summerscale, Kate, 1965- (Penguin Press, 2021)
"London, 1938. In the suburbs of the city, a young housewife has become the eye in a storm of chaos. In Alma Fielding's modest home, china flies off the shelves and eggs fly through the air; stolen jewellery appears on her fingers, white mice crawl out of her handbag, beetles appear from under her gloves; in the middle of a car journey, a turtle materializes on her lap. The culprit is incorporeal. As Alma cannot call the police, she calls the papers instead. After the sensational story headlines the news, Nandor Fodor, a Hungarian ghost hunter for the International Institute for Psychical Research, arrives to investigate the poltergeist. But when he embarks on his scrupulous investigation, he discovers that the case is even stranger than it seems. By unravelling Alma's peculiar history, Fodor finds a different and darker type of haunting, a tale of trauma, alienation, loss and revenge. He comes to believe that Alma's past has bled into her present, her mind into her body. There are no words for processing her experience, so it comes to possess her. As the threat of a world war looms, and as Fodor's obsession with the case deepens, Alma becomes ever more disturbed. With characteristic rigor and insight, Kate Summerscale brilliantly captures the rich atmosphere of a haunting that transforms into a very modern battle between the supernatural and the subconscious"--